Identifikasi Senyawa Alkaloid Pada Daun Bidara Arab (Ziziphus spina-christi L.) Menggunakan Metode Spektrofotometri UV-Vis - A. Mu’thi Andy Suryadi; Mohammad Adam Mustapa; Nur Khofifah Zahrah (Jurusan Farmasi Universitas Negeri Gorontalo, 2022)
Christ's torn jujube (Ziziphus spina-christi L.) is a medicinal plant that has many benefits for curing or treating diarrhea, fever, and cancer. One of the compounds that play role is an alkaloid. This study was generated to identify the alkaloid compounds in the leaves of the Christ’s jujube torn using the UV-Vis spectrophotometry method. Christ's torn jujube leaves were macerated using 3 types of solvents with different polarity levels i.e., n-hexane, ethyl acetate, and methanol. Furthermore, phytochemical screening of alkaloid compounds was carried out. A Christ jujube leaf sample that was positive for alkaloids was found in the ethyl acetate extract; then identified using thin layer chromatography with eluent n-hexane: ethyl acetate (8:2), yielding 4 points with an Rf value of 0.25; 0.4 ; 0.52 ; and 0.62. Furthermore, phytochemical screening of alkaloid compounds was carried out. Christ' torn jujube which were positive for alkaloids present in the ethyl acetate extract were identified using thin layer chromatography with n-hexane eluent: ethyl acetate (8:2), yielding four spots with an Rf value of 0.25; 0.4 ; 0.52 ; and 0.62. The four spots were identified using UV-Vis spectrophotometry, obtained a wavelength of 248 ; 268 ; 268 ; and 255. Based on the identification results on the leaf extract, each stain was suspected to contain cantin-6-one alkaloid compounds.